2021
DOI: 10.4317/jced.58033
|View full text |Cite
|
Sign up to set email alerts
|

Salivary characteristics may be associated with burning mouth syndrome?

Abstract: Background Burning mouth syndrome (BMS) it is characterized by burning and uncomfortable sensations with no clinical alterations or laboratory findings. The evaluation of the salivary characteristics of people with BMS can help the understanding of the pathogenesis of this condition. This case-control study aimed to trace the salivary profile of women with burning mouth syndrome (BMS). Material and Methods 40 women with BMS and 40 control women were recruited. Unstimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…ELISA technique was used to analyze salivary biomarkers in seven studies (Aitken-Saavedra et al, 2021;Borelli et al, 2010;Boucher et al, 2017;Lončar-Brzak et al, 2020;Lopez-Jornet et al, 2020;Nosratzehi et al, 2017;Pekiner et al, 2009), immunohistochemistry in two studies (Amenábar et al, 2008;Tvarijonaviciute et al, 2017), and immunoassay in five studies (Boras et al, 2010;Dias Fernandes et al, 2009;Imura et al, 2016;Kim et al, 2012;Zidverc-Trajkovic et al, 2009). The remaining studies analyzed biomarkers with techniques such as Multiplex (Lopez-Jornet et al, 2020), spectrophotometry (López-Jornet et al, 2014;Nosratzehi et al, 2017;Salarić et al, 2017), and colorimetric kits (Borelli et al, 2010;de Moura et al, 2007;Kim et al, 2012;Lopez-Jornet et al, 2020;Table S2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISA technique was used to analyze salivary biomarkers in seven studies (Aitken-Saavedra et al, 2021;Borelli et al, 2010;Boucher et al, 2017;Lončar-Brzak et al, 2020;Lopez-Jornet et al, 2020;Nosratzehi et al, 2017;Pekiner et al, 2009), immunohistochemistry in two studies (Amenábar et al, 2008;Tvarijonaviciute et al, 2017), and immunoassay in five studies (Boras et al, 2010;Dias Fernandes et al, 2009;Imura et al, 2016;Kim et al, 2012;Zidverc-Trajkovic et al, 2009). The remaining studies analyzed biomarkers with techniques such as Multiplex (Lopez-Jornet et al, 2020), spectrophotometry (López-Jornet et al, 2014;Nosratzehi et al, 2017;Salarić et al, 2017), and colorimetric kits (Borelli et al, 2010;de Moura et al, 2007;Kim et al, 2012;Lopez-Jornet et al, 2020;Table S2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In this complex scenario, the study of salivary biomarkers in patients with BMS could help in the diagnostic process and in the evaluation of response to treatment. Multiple studies (Aitken‐Saavedra et al, 2021; Amenábar et al, 2008; Borelli et al, 2010; Boucher et al, 2017; Dias Fernandes et al, 2009; Kang et al, 2017; Kim et al, 2012; Lončar‐Brzak et al, 2020; Lopez‐Jornet et al, 2020; Salarić et al, 2017) have investigated several salivary biomarkers in patients with BMS, but to date, none has been introduced into clinical practice. It is noteworthy how saliva is an accessible fluid.…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies argued that xerostomia in patients with BMS is merely a subjective symptom or caused by side effects of medications, rather than by actual alterations to salivary gland function [ 3 ]. In contrast, other recent studies demonstrated that patients with BMS have significantly lower unstimulated salivary flow rates than control subjects regardless of medications, whereas no significant difference was found in stimulated salivary flow rates between them [ 10 , 11 , 32 , 33 ]. Unstimulated salivary flow reflects the basal level of salivary flow in a resting status, and approximately 70% of unstimulated saliva derives from the submandibular and sublingual glands, while most of stimulatory saliva is excreted from the parotid glands [ 34 ].…”
Section: Discussionmentioning
confidence: 64%
“…Xerostomia in patients with BMS has usually been considered a perceived symptom related to somatosensory dysfunction, rather than actual hyposalivation [ 9 ]. However, several recent studies have demonstrated a reduced unstimulated salivary flow rate with different saliva characteristics and proteomic profiles in patients with BMS as compared with healthy subjects [ 10 , 11 , 12 ]. A recent systemic review study regarding salivary characteristics in patients with BMS has also suggested that BMS is associated with changes in salivary biomarkers of inflammation and oxidative stress [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dada la relación entre xerostomía y SBA, Tan et al (2021) sugieren que la hipofunción glandular podría ser un factor contribuyente, por ello recomiendan el uso de urea y lisozima lactoperoxidasa (Biotène) que, si bien aumentan la humedad y lubricación de la cavidad oral, no han demostrado ser eficaces frente al dolor [20,23].…”
Section: Diagnósticounclassified